Karakteristik Perumahan dan Permukiman di Pesisir Sungai Desa Pohuwato Timur - Nurmiah, Nurmiah; Umar, Indriani (JARI: Journal of Architecture, Research and Innovation, 2025)
By raising one case of observation of the coastal settlements of Marisa River and Delo Lake in Gorontalo which are very unique and quite complex, this is due to its demographic characteristics, diversity of land functions and morphological structure of its building patterns. However, as a result of the heavy burden of the environment/area and the complexity of existing activities, there is a conflict of interest that creates degradation of buildings and the environment along with its environmental infrastructure, so that the development process gives rise to many conflicts of interest. The gap in government supervision, inadequate facilities and infrastructure, low control of water and sanitation, low coordination and placement between public and private buildings further add to the chaos of problems that lead to environmental decline. This study aims to describe the spatial patterns and characteristics of housing and settlements on the coast of Marisa River and Delo Lake and explain the factors that cause and influence them. A descriptive qualitative approach with observation methods, namely observing the entire residential area and then determining the spatial boundaries of house groups. Data are analyzed with reference to theories and conditions that strengthen the findings. The results of the study show that first, the pattern created between houses and roads is that houses grow in groups following the road with the orientation of the houses to the road facing each other and back to back. The pattern of houses along the river grows longitudinally or linearly, following the physical conditions of the environment bounded by the river. Overall, the spatial pattern of housing and settlements along the lakeshore forms an organic pattern that grows increasingly westward, approaching Lake Delo. Factors influencing this pattern include nature (climate), the social environment, and the physical conditions of the surrounding environment.